Hypothermia - Ipekci, Afsin; Çakmak, Fatih (Cerrahpaşa Medical Journal, 2023)
A decrease in body temperature below 35°C (<95°F) is defined as hypothermia. Accidental hypothermia occurs when a person’s body temperature drops involuntarily as a result of exposure to cold. Thousands of people lost their lives due to both trauma and hypothermia in natural disasters such as earthquakes, tsunamis, avalanches, and floods. In hypothermia, depending on the degree of body temperature, the functions of the body systems are suppressed. The staging of hypothermia classifications was made based on the measurement of core temperature, clinical symptoms, and risk of cardiac arrhythmia. The main precautions for hypothermic patients in the prehospital setting are removal from the cold environment, insulation, rewarming, and rapid transfer to the hospital. The most effective internal rewarming strategy is extracorporeal life support in the hospital setting Cite this article as: Ipekci A, Çakmak F. Hypothermia. Cerrahpaşa Med J 2023;47(S1):27-32.